(untitled) (LEARNing Landscapes, 2009)
Literacy teaching and learning and education more generally seem destined to be buffeted by periodic pendulum swings between more and less regulation of curriculum, assessment and teachers’ work. Reflecting from a position of seniority, I speculate in this commentary on how the trajectory of progressive and generative theories and practices in literacy education might have been altered if such swings had not been so pervasive over the past several decades. Drawing on insights that have guided my own thirty-plus years of work to advance critically reflective and progressive literacy education, I suggest that greater attention to some wise words from past decades might help today’s educators to resist the never-ending pull of the pendulum.